KECEMASAN SAAT MENGIKUTI PRAKTIKUM LABORATORIUM DIMASA PANDEMI COVID-19 DENGAN MEKANISME KOPING - Ailine Yoan Sanger; Anggraini Agustina Ayomi (Fakultas Ilmu Keperawatan Universitas Klabat, 2022)
AbstractAnxiety is a feeling of worry and fear experienced by individuals associated with laboratory practicums during the COVID-19 pandemic which can cause mental health problems if not addressed. In overcoming anxiety problems, individuals will use strategies in problem solving, namely coping mechanisms. The purpose of this study was to determine the relationship between anxiety and coping mechanisms. The method used is cross sectional, with pearson correlation statistical test. The sampling technique used a probability sampling technique with a random sampling of 172 respondents. The results of the study was the majority 90 (52.3%) respondents experienced mild anxiety. In terms of anxiety, as many as 162 (94.2%) respondents used adaptive coping mechanisms. It was found that there was a significant relationship between anxiety and coping mechanisms in students with p = 0.000 and r = -0.381. This means that the lower a person's anxiety, the person's coping mechanism leads to an adaptive coping mechanism. The results of this study are expected to be a reference for further researchers in dealing with student anxiety during the COVID-19 pandemic in order to maintain adaptive coping mechanisms to overcome anxiety due to the pandemic.Keywords: Anxiety, COVID-19, Laboratory Practicums, PandemicAbstrakKecemasan merupakan perasaan khawatir dan takut, dialami individu yang berhubungan dengan praktikum laboratorium dimasa pandemi COVID-19 yang dapat menimbulkan masalah kesehatan mental jika tidak diatasi. Dalam mengatasi masalah kecemasan, individu akan menggunakan strategi dalam penyelesaian masalah yaitu mekanisme koping. Tujuan dari penelitian ini untuk mengetahui hubungan kecemasan saat mengikuti praktikum laboratorium di masa pandemi COVID-19 dengan mekanisme koping. Metode yang digunakan yaitu cross sectional, dengan uji statistik pearson corellation. Teknik pengambilan sampel menggunakan teknik probability sampling dengan pengambilan sampel secara acak berjumlah 172 responden. Hasil penelitian didapati mayoritas 90 (52.3%) responden mengalami cemas ringan. Dalam hal kecemasan, sebanyak 162 (94.2%) responden menggunakan mekanisme koping yang adaptif. Didapati terdapat hubungan yang signifikan antara kecemasan dengan mekanisme koping pada mahasiswa dengan nilai p = 0.000 dan nilai r = -0.381. Artinya adalah semakin rendah kecemasan seseorang, mekanisme koping seseorang mengarah kepada kepada mekanisme koping yang adaptif. Hasil penelitian ini diharapkan menjadi acuan untuk peneliti selanjutnya dalam menghadapi kecemasan mahasiswa dimasa pandemi COVID-19 agar tetap mempertahankan mekanisme koping yang adaptif untuk mengatasi kecemasan akibat pandemic.Kata Kunci: COVID-19, Kecemasan, Pandemi, Praktikum Laboratorium